Emotional Distress Among Pediatric Cancer Patients and their Siblings - Manzoor, Ruqayya; Yasmeen, Nuzhat; Shaheen, Hijab; Mushtaq, Nazia (Journal of Rawalpindi Medical College, 2023)
Objectives: Cancer being a serious chronic illness, causes profound effects on physical and mental health of the individual as well as affects their caregivers and family members’ mental health. This study aims to find out the burden of emotional distress in patients of childhood cancer as well as their healthy siblings. Methods: It was a descriptive cross-sectional study. Parents of the children undergoing cancer treatment or having completed treatment within past one year were asked to complete an interview proforma (Pediatric Emotional Distress Scale) about their child’s behaviour over past one month, scoring each behaviour on a scale of 1 to 5 according to the frequency of symptoms. The data was then analysed using SPSS 20. The frequency distribution, central tendencies and standard deviations were calculated accordingly. Results: Almost eighty-five% of the patients showed scores above the clinical threshold for emotional distress. Eighteen% of the healthy siblings also had scores above the clinical threshold. Patients as well as their healthy siblings showed high levels of anxiousness in their behaviours. Conclusions Childhood cancer is a cause of major emotional trauma in patients. Age-matched siblings usually cope well with the illness.